Monetary Integration, Uncertainty and the Role of Monetary Policy - Graham M. Voss (Queen's University, Department of Economics, 1991)
This research considers the positive theory of monetary integration in a general equilibrium monetary model of the world economy. The analysis demonstrates that, in the face of uncertainty and incomplete asset markets, participation in a monetary union may be welfare improving since it facilitates state-dependent resource transfers between regional economies. Such resource transfers are used to optimally reduce the variance of consumption for a risk averse agents. This potential for improving welfare depends not only on the agents' risk aversion but on the interrelationship of the regional economies: contrary to Mundell (1961), economically diverse regions may be well suited to a common currency.
Keywords: 330